2014
DOI: 10.1007/s11356-014-4018-x
|View full text |Cite
|
Sign up to set email alerts
|

Correlating concentrations of heavy metals in atmospheric deposition with respective accumulation in moss and natural surface soil for ecological land classes in Norway between 1990 and 2010

Abstract: This study investigated whether statistical correlation of modeled atmospheric heavy metal deposition and respective accumulation in moss and natural surface soil varies across natural landscapes in Norway. Target metals were cadmium, lead, and mercury, and analyses were run between 1990 and 2010 on a 5-year interval. The landscape information was derived from the Ecological Land Classification of Europe. Correlations between concentration and respective deposition data were computed for each land class. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 37 publications
0
4
0
1
Order By: Relevance
“…It has been claimed by some (Reimann et al, 2009) that the steep gradient evident in surface soil composition along a south-north gradient in southern Norway is due to natural conditions related to climate and vegetation. This view is not supported by results from a recent statistical study in Norway including the geographical distribution of ecological land classes (Nickel et al, 2014) where it is concluded that atmospheric transport is a main source of Pb and Cd accumulation in moss as well as in natural surface soil.…”
Section: Discussionmentioning
confidence: 63%
“…It has been claimed by some (Reimann et al, 2009) that the steep gradient evident in surface soil composition along a south-north gradient in southern Norway is due to natural conditions related to climate and vegetation. This view is not supported by results from a recent statistical study in Norway including the geographical distribution of ecological land classes (Nickel et al, 2014) where it is concluded that atmospheric transport is a main source of Pb and Cd accumulation in moss as well as in natural surface soil.…”
Section: Discussionmentioning
confidence: 63%
“…As can be seen from Table 4, in the first and second stages, the hubs and authorities of the Nordic green patent citation networks are mainly aimed at the prevention and control of mercury pollution, such as removing mercury vapor from exhaust gas (4273747A), extracting and recovering mercury from gas (4233274A), controlling mercury emissions (6855859B2), etc. This is mainly due to the accumulation of highly concentrated mercurybased air pollutants in Nordic countries located at high latitudes, and their diets are inseparable from fish and aquatic products, which is considered to be the main way of human methylmercury exposure [53]. Therefore, the Nordic countries have attached great importance to the prevention and control of mercury pollution as early as the end of the twentieth century, and the related technologies have also flourished.…”
Section: Evolution Analysis Of Key Nodesmentioning
confidence: 99%
“…Зокрема, у країнах Європи для Сd та Hg було продемонстровано тісну кореляцію між згаданими параметрами [91]. Подібний висновок також було зроблено для Mn [21] та Pb [74]. Крім того, за результатами масових аналізів (десятків тисяч) вмісту Cd, Hg та Pb у мохах, повітрі, ґрунті та інших компонентах біогеоценозів у Європі було визначено фактори, які суттєво впливають на концентрацію згаданих важких металів у мохах, у т.ч.…”
Section: мохоподібні (Bryobionta) як тест-об'єкти бріогеохімічної інди-кації атмосферних випадань важких металів та радіонуклідів у навкоunclassified